Panel data analysis of the effects of female labor force participation on profit rates - Adem Yavuz Elveren; Cameron Davis; Josh Budd (International Econometric Review (IER), 2022)
It is expected that increasing female labor force participation (FLFP) rate, due to the gender wage gap, reduces the unit labor costs, and therefore increases profit rates. Using a dataset of 130 countries for 1990-2019, this paper shows that while FLFP increases profit share in highincome countries, it reduces in middle-income countries. However, for both middle- and highincome countries, FLFP cannot prevent the overall tendency in profit rates to decline caused by a consistent decline in output-capital ratio.
Keywords: B54; C01; E24; 330; Female labor force participation; profit rate; profit share; output-capital ratio